Analisis Pengaruh Pakan Fermentasi terhadap Pertumbuhan Sapi Potong - Husna Oke (Journal of Animal Husbandry, 2025)
This study aims to analyze the effect of fermented feed on the growth performance of beef cattle. Fermented feed is known to improve nutrient digestibility and enhance rumen microbial activity, which can support better weight gain and feed efficiency. The research was conducted at a local cattle breeding farm in West Sumatra using a randomized block design with three treatment groups: conventional feed, partially fermented feed, and fully fermented feed. Each group consisted of 10 beef cattle aged 12–18 months. Data on average daily gain (ADG), feed conversion ratio (FCR), and body condition score (BCS) were collected over 90 days. Results showed that cattle receiving fully fermented feed had a significantly higher ADG (0.89 kg/day) compared to conventional feed (0.65 kg/day). Moreover, FCR improved by 18% in the fully fermented group. These findings suggest that fermented feed positively influences growth performance, enhances feed efficiency, and provides potential economic benefits for beef cattle farmers. The study concludes that fermented feed can be applied as an alternative feeding strategy to optimize beef cattle production in smallholder farming systems.